2019
DOI: 10.3844/ajbbsp.2019.125.137
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, Partial Identification and Bioactivities of Total Flavonoids from Carex meyeriana Kunth

Abstract: To date, knowledge associated with extraction, chemical constituents and bioactivities of Total Flavonoids from Carex meyeriana Kunth (TFCMK) that remains unclear. Therefore, this paper was designed to optimize the ethanol reflux extraction method by response surface methodology and determine the chemical constituents by Liquid Phase-Mass Spectrometry (HPLC-MS); additionally, the bioactivities including antioxidant, antibacterial and hemolysis test were also explored. The maximum TFCMK extraction yield of 6.24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Flavonoids are polyphenols with various biological activities in plant secondary metabolism, widely distributed in various parts of the plant body. Some researchers have confirmed that flavonoids have a wide range of active functions, including alleviating aluminum phosphideinduced anemia in rats (Afolabi et al, 2019), enhancing the antioxidant status of the ovaries; antibacterial and antioxidant activities (Wang et al, 2019;Zhang et al, 2021), etc.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Flavonoids are polyphenols with various biological activities in plant secondary metabolism, widely distributed in various parts of the plant body. Some researchers have confirmed that flavonoids have a wide range of active functions, including alleviating aluminum phosphideinduced anemia in rats (Afolabi et al, 2019), enhancing the antioxidant status of the ovaries; antibacterial and antioxidant activities (Wang et al, 2019;Zhang et al, 2021), etc.…”
Section: Flavonoidsmentioning
confidence: 99%